Characterization of the Liriodendron Chinense MYB Gene Family and Its Role in Abiotic Stress Response - Wu, Weihuang; Zhu, Sheng; Zhu, Liming; Wang, Dandan; Liu, Yang; Liu, Siqin; Zhang, Jiaji; Hao, Zhaodong; Lu, Ye; Cheng, Tielong; Shi, Jisen; Chen, Jinhui (Frontiers in Plant Science, 2021)
Liriodendron chinense (Lchi) is a Magnoliaceae plant, which is a basic angiosperm left behind after Pleistocene and mainly distributed in the south of the Yangtze River. Whether it can adapt to different environmental conditions, such as drought，high temperature, and low temperature, and the molecular mechanism are not very clear. Among plant transcription factors (TFs), the MYB gene family is one of the largest that often involved in stress of adversity response signaling, growth, and development. Therefore, studying if and how the MYB TF regulates abiotic stress signaling, growth, and development in Lchi should be informative in showing how this tree deals with such stressful conditions. In our research, the genome-wide analysis of the Liriodendron chinense (Lchi) MYB genes family was performed, containing the phylogenetic relationship tree, gene exon-intron structure, collinearity, and chromosomal position. According to the evolutionary tree, 190 LchiMYBs were divided into three main branches. We found the LchiMYBs to be evenly distributed across 19 chromosomes, with their collinearity suggesting that segment duplication may contribute to LchiMYB gene expansion. We used 8 tissue transcriptome, 11 stages somatic embryogenesis transcriptome, and cold, heat, drought stress leaf transcriptome to analyze the function of the MYB gene. The results of tissue expression showed that most LchiMYB genes regulated bark, leaf, bud, sepal, stigma, and stamen, as well as the four important stages (ES3, ES4, ES9 and PL) of somatic embryogenesis. More than 60 LchiMYBs responded to heat, cold, and drought stress, some of which have undergone gene duplication during evolution. LchiMYB3 was highly expressed under all three forms of stress, while LchiMYB121 was strongly induced by both cold and heat stress. Eight genes selected for different expression patterns were also verified by qRT-PCR experiments. The results suggest that these LchiMYBs may regulate Liriodendron chinese growth development and resistance against abiotic stress. This study shows that in Liriodendron chinense, cross regulatory function of LchiMYB in growth and development, asexual reproduction, and abiotic resistance. This information will prove pivotal in directing further studies on the biological function of the Liriodendron chinense MYB TF in genetic improvement and abiotic stress response.